2006
DOI: 10.1590/s0037-86822006000500001
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing human asymptomatic visceral leishmaniasis in an urban area of the State of Minas Gerais, using serological and molecular biology techniques

Abstract: A population-based cross-sectional study was set up in Sabará country, Southeastern Brazil, to identify asymptomatic human visceral leishmaniasis in an urban area of low disease prevalence. Blood was collected on filter paper (n=1,604 inhabitants) and examined by indirect immunofluorescent test, enzyme-linked immunosorbent assay and immunochromatographic strip test. The prevalence rates of infection ranged from 2.4 to 5.6% depending on the test used. One year later, venous blood was collected in a subset of 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
37
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 33 publications
4
37
0
Order By: Relevance
“…A lower quantity of antibodies in these subjects with asymptomatic infection may explain the lighter impression on the immunochromatographic strip. This observation was also made by Moreno and others, 25 who established, for the diagnosis of asymptomatic infection by TRALd, that the test result should interpreted by three observers. The authors found wide disagreement between assessments and low reproducibility of the results (κ = 0.14).…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…A lower quantity of antibodies in these subjects with asymptomatic infection may explain the lighter impression on the immunochromatographic strip. This observation was also made by Moreno and others, 25 who established, for the diagnosis of asymptomatic infection by TRALd, that the test result should interpreted by three observers. The authors found wide disagreement between assessments and low reproducibility of the results (κ = 0.14).…”
Section: Discussionsupporting
confidence: 52%
“…The authors found wide disagreement between assessments and low reproducibility of the results (κ = 0.14). 25 This bias might explain the low agreement between the TRALd and ELISArK39 results, because both tests use the same antigen. In the present study, we observed the best κ agreement between the results of tests that use similar antigens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, sensitivity of these methods decreases because of low antibody levels in bloods of asymptomatic patients. 6,11,12 One of the most sensitive and specific methods in the diagnosis of VL is polymerase chain reaction (PCR). For diagnosing patients with clinical symptoms, PCR has 90% and greater sensitivity, 13 whereas microscopic methods and blood culture have 70.5% and 74.5% sensitivity, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…However, this technique also detected positive results for subjects living in areas of endemicity but who did not progress to classic disease. In addition, there was frequent disagreement between the results of serological tests and PCR (12)(13)(14)(15)(16).…”
mentioning
confidence: 99%